Endoscopic trans gastric assisted surgery for gastric tumors: Case report and description of a new surgical technique. (2020) - Solano, Jaime; Cadena, Manuel; Vergara, Arturo; Cabrera, Luis Felipe; Herrera, Gabriel; Pedraza, Mauricio
Highlights: Laparoscopic intragastric surgery is a possible management for gastrointestinal storm tumors(GIST) treatment. EPATS as percutaneous endoscopic intragastric surgery (PEIGS) can salvage the entire stomach of patients with sub epithelial lesions. Abstract: Background: Minimally invasive intragastric surgery [IGS] was first described by Ohashi in 1995 for early gastric cancer, with 3 trocars placed in the gastric lumen. Prior abdominal surgery is not a contraindication to IGS while the abdominal cavity is not explored, always that exist transilumination. But conversion to laparoscopic and open surgery can be challenging owing to the insufflated stomach and/or small bowel, although gas can be easily released via the gastrostomy. Case presentation: A 53-year-old female patient, presented with a sub epithelial gastric antrum lesion confirmed by endoscopic ultrasonography managed with surgical endoscopic percutaneous assisted transgastric technique [EPATS] using a gastrostomy tube and the endoscope. Discussion: We have been developing this operation since 2018. Nevertheless, we think EPATS is worthy to master, as PEIGS can salvage the entire stomach of patients with sub epithelial lesions in the lesser curve and in the esophagogastric junction, who otherwise would have to undergo total or proximal gastrectomy. Conclusion: We need to perform more cases for future comparative studies with percutaneous endoscopic intragastric surgery [PEIGS] in terms of parameters as pain, inflammation, complications, stenosis, oncological results and cosmesis.